History and Development of the Education Curriculum before the Reformation - Bunaya; Firman Ashari (Penerbit Hellow Pustaka, 2024)
The curriculum is the most important element in developing educational performance, because basically education that does not adhere to the curriculum will be difficult to systematize in its implementation. The curriculum before the reformation has undergone several changes including starting from the old order in 1947 where the curriculum was known as Rantjana Pelajaran then followed in 1952, so that the curriculum changed to Rentjana Terurai. Then the third change in 1964, this curriculum was named the education plan which focused on moral development, emotional intelligence, skills and physical (pancawardhana). And different during the new order period, during this period the curriculum underwent changes starting in 1968, this curriculum was named the 1968 curriculum from the results of the evaluation of pancawardhana which was refined into panca jiwa pancasila, then the second change began in 1975 which focused on the development of instructional systems (PPSI). The third turn was in 1984 and was named the 1984 curriculum which focused on skill development with a model called CBSA (how to learn active students), while the fourth turn was in 1994 which is known as the 1994 curriculum. In essence, all curricula that are applied must undergo changes, which can thus adapt to the development and needs of society in the future.